1990
DOI: 10.1182/blood.v76.1.254.254
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hepatitis C virus antibody in a cohort of hemophilia patients [see comments]

Abstract: One hundred thirty-one patients followed at the New England Hemophilia Center (Worcester, MA) were tested for antibody to hepatitis C virus (HCV). All but two had used factor concentrate that had not undergone viral inactivation; two patients had used only cryoprecipitate. The overall prevalence of HCV antibody positivity was 76.3%. There was no significant difference in age or the amount of non-heat-treated factor concentrate used between the group that was HCV antibody positive and negative. There was also n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
61
0
1

Year Published

1991
1991
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(66 citation statements)
references
References 17 publications
4
61
0
1
Order By: Relevance
“…As shown in table 1,22 children (62.9%) seroconverted during follow-up. This percentage is similar to that obtained in haemophilic patients [8]. At the time of seroconversion they had received a mean of 83.9 f 60.7 blood units (median 68.5); 13 patients (37.1%) remained negative.…”
Section: Prevalence Of Hepatitis C Virus Antibody In Beta-thalassemicsupporting
confidence: 84%
“…As shown in table 1,22 children (62.9%) seroconverted during follow-up. This percentage is similar to that obtained in haemophilic patients [8]. At the time of seroconversion they had received a mean of 83.9 f 60.7 blood units (median 68.5); 13 patients (37.1%) remained negative.…”
Section: Prevalence Of Hepatitis C Virus Antibody In Beta-thalassemicsupporting
confidence: 84%
“…Other authors described these associations between hepatitis C and HIV and HBV infections in similar populations with haemophilia. 8,31,32 In addition, this study confirms the markedly increased risk of chronic HCV infection is a significant health problem in the remainder. 33 Progressive fibrosis can lead to clinically significant liver disease including cirrhosis, end-stage liver disease and hepatocellular carcinoma.…”
Section: Discussion and Con Clus I Onsupporting
confidence: 77%
“…[5][6][7] Before the introduction of viral-inactivated products, most patients with haemophilia were treated with cryoprecipitate, fresh frozen plasma and plasma-derived clotting factor concentrates during the 1970s and 1980s and they were unfortunately infected with HCV. 7,8 Previous cohort studies of HCV-infected patients with haemophilia indicated an increasing burden of HCV-associated liver disease in these patients with inherited bleeding disorders. 6,9,10 In Brazil, the country with the fourth largest haemophilia population in the world, lyophilized concentrates of factors VIII (FVIII) and IX (FIX), became systematically available for replacement therapy only in 1994, after the introduction of manufacturing viral inactivation procedures.…”
Section: Introductionmentioning
confidence: 99%
“…In transfusion-associated non-A non-B hepatitis, antibodies to HCV have been detected as early as 10 weeks after exposure, using a standard enzyme-linked immunosorbent assay (ELISA) [43]. In haemophiliacs the presence of anti-HCV does not appear to be related to severity of liver damage, ALT level or stage of HIV infection [44,45]. In a number of .HIV-infected haemophiliacs HCV 'seroreversion' has been reported despite persistent infection with HCV, determined by detection of viral RNA by PCR [46].…”
Section: Hcv Serologymentioning
confidence: 99%